Electrifying Consumer Choices: Unveiling the Road to Green Intentions and EV Adoption - Jeffyan Alberto; Fahrul Riza (Journal of Consumer Sciences, 2023)
Electric vehicles (EVs) are considered to combat environmental issues globally, including Indonesia, where transportation is believed to contribute to air pollution and greenhouse gas emissions. This study analyzed consumers’ attitudes and intentions to purchase electric vehicles in Jakarta by focusing on environmental concerns, perceived usefulness, and incentives. Descriptive quantitative data were used in this study. Data were collected from 156 respondents using a questionnaire with a purposive sampling technique and analyzed using structural equation modeling with SmartPLS. The study found that environmental concerns, perceived usefulness, and incentives positively and significantly affected consumer attitudes. Consumer attitudes mediate the relationship among perceived usefulness, incentives, and purchase intention, indicating that information about electric vehicles and incentives can shape positive consumer attitudes and lead to positive purchase intentions. However, environmental concerns only affect consumer attitudes and do not directly affect purchases. Therefore, it is recommended to better explain the benefits of electric vehicles in terms of environmental protection and cost efficiency, as well as incentive policies for purchasing electric vehicles, to influence consumer behavior and purchase intentions.